2022
DOI: 10.3390/app122010571
|View full text |Cite
|
Sign up to set email alerts
|

Review of Visualization Technique and Its Application of Road Aggregates Based on Morphological Features

Abstract: The sustainable performance of asphalt pavement depends on the quality and mix design of road aggregates. Identifying aggregate morphology and size is a prerequisite step for material design and numerical modeling of asphalt mixtures. The paper aims to review the morphometric measurement, characteristic parameters and visualization technique of road aggregates. Types, calculation methods and advantages of aggregate morphological characteristics are highlighted. The applications of aggregate morphological featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 177 publications
0
4
0
Order By: Relevance
“…Recently, as dynamic image analysis has been shown to be useful and convenient for particle analysis, it was adopted in numerous studies, such as Buckland et al [36], Guo et al [37], Li and Iskander [38], etc. Visual techniques for morphological analysis are extensively discussed in Wang et al [4]. We used a Microtrac Camsizer XL (the operating scheme is presented in Figure 4), which is a quasi-3D dynamic image analyser used for particle characterization.…”
Section: Dynamic Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, as dynamic image analysis has been shown to be useful and convenient for particle analysis, it was adopted in numerous studies, such as Buckland et al [36], Guo et al [37], Li and Iskander [38], etc. Visual techniques for morphological analysis are extensively discussed in Wang et al [4]. We used a Microtrac Camsizer XL (the operating scheme is presented in Figure 4), which is a quasi-3D dynamic image analyser used for particle characterization.…”
Section: Dynamic Image Analysismentioning
confidence: 99%
“…The overall outer appearance of a rock particle (rock clast) can be described at different shape aspect levels [1][2][3][4]. If we observe particles' macro features, their shape aspects can be divided into form and roundness/angularity.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of concrete are affected by many factors, such as temperature and loading ratio [11,12]. Previous studies demonstrated that the reasonable composition ratio of mineral admixtures and recycled aggregates can greatly improve the performance of composite admixtures [13][14][15]. On the one hand, the compaction method and microstructure of concrete are also important factors affecting its performance [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is the type of aggregate which determines the modulus especially strongly [ 2 , 3 , 4 ]. That is why the relationship between the modulus and compressive strength of concrete is not sufficient without taking into consideration the aggregate type [ 5 , 6 ]. In the case of normal-weight concrete (NWAC), EN-1992-1-1 [ 1 ] considers corrections of a value of modulus of elasticity in terms of aggregate type.…”
Section: Introductionmentioning
confidence: 99%